Spherical nucleic acid and application thereof in preparation of hepatic fibrosis drugs - LIU WENJIA; HE WANGXIAO (2024)
The invention belongs to the technical field of biological medicines, and discloses spherical nucleic acid and application thereof in preparation of hepatic fibrosis medicines. The miR-325-3p nucleic acid is obtained through screening, it is verified that the nucleic acid has an important influence effect in the stage that liver blood sinus endothelial cells are subjected to endothelial-to-mesenchymal conversion, capillary vascularization of the liver blood sinus endothelial cells can be effectively reversed by applying the miR-325-3p simulant, and the miR-325-3p mimulant has the application prospect of preparing the liver fibrosis medicine. 本发明属于生物医药技术领域，公开了一种球形核酸及其在制备肝纤维化药物中的应用。本发明筛选得到了miR-325-3p核酸，验证了该核酸在肝血窦内皮细胞经历内皮到间充质转化阶段具有重要影响作用，应用miR-325-3p模拟物能有效逆转肝血窦内皮细胞的毛细血管化，具有制备肝纤维化药物的应用前景。